Idioms description, comprehension, acquisition, and pedagogy - Liu, Dilin (ESL & applied linguistics professional series, 2008)
Covers idiom use, learning, and teaching. This work approaches the topic with a balance of theory and research in cognitive linguistics, psycholinguistics, corpus linguistics, and sociolinguistics combined with informed teaching practices. It also includes discussion of idiom definition, classification, usage patterns, and functions.